Simulation Model for Rainfall Intensity to Landslide Susceptibility - Lutfi, Nurul Adibah; Ahmad, Mustaffa Anjang; Maha Agung, Putera Agung; Sedayu, Agung; Abdullah, Nazirah Muhamad (Journal of Applied Civil Engineering and Infrastructure Technology, 2024)
Landslides are one of the most hazardous natural disasters because their occurrences are often destructive to natural and artificial structures on earth and reduce, the quality of the surrounding environment. Predicting the susceptibility of an area to landslides is essential for reducing losses in terms of property, human lives, and environmental damages. Kota Wisata Batu (KWB) is one of areas which having a highest landslide potential in East Java, Indonesia, recording data mentioned that there are 109 landslides in 2022 caused by highest rainfall intensity of 502 mm with a number of intensities of 2977mm per year. Study purposed to identify the factors contributing to landslide occurrences using a geodetic measurement method. The study uses geographic information system (GIS) and PRISMA software analyses to examine and/ or evaluate the relationship between rainfall intensity and landslide susceptibility. The study results the generation of rainfall patterns and maps highlighting sensitivity areas to landslides. These visual representations the classification area as a high-risk and susceptibility zone to landslides at Kota Wisata Batu, East Java. January to April, and August to November should have pay attention since these months is reflection of monsoonal climate with the hard rain in a few days without the raining pause. Some places which are required to pay attention, such as: Gunungsari, Tulungrejo, and Songgokerto.